Factors Affecting Work Accidents Among Electrical Network Maintenance Workers: A Systematic Literature Review - Hijratul Ullia; Hanifa Maher Denny; Suroto Suroto (Jurnal Ners, 2026)
Work acciden during the electrical maintenance directly affect the health of the employees, productivity losses, and company losses because of lost assets. A number of elements contribute to accidents, and by understanding these aspects, workers can take protective actions before an electrical disaster occurs. The "PRISMA" technique, which stands for recommended reporting items for systematic reviews and meta-analyses, was used to conduct the study. According to the study findings, electrical accidents are caused by two factors: personal factors (personal stress, fatigue, social support, work stress, and self-extremity) and safety climate factors (safety participation, safety compliance, safety training, safety knowledge, safety motivation, work environment, and work procedures). Thus, it can be said that personal variables and climate safety elements are the main causes of electrical accidents.